Standards update routing for optical networks. - Bernstein, G. (IEEE Communications magazine)
We focus on a component of the optical control plane: routing. We give a quick overview of what routing functionality can mean in the optical control plane and compare that with routing in IP networks. We also look at this functionality from the point of view of a carrier running an optical network. We point out some areas of potential disagreement and give an update of the status of optical routing at the various standards bodies.